Problem Based Learning sebagai Metode Pembelajaran yang Kontekstual - Polii, Hendra (Zenit, 2015)
Problem-based learning is a teaching method that is different from the traditional learning methods. The emphasis is on the process. In the learning process, in particular the knowledgetransfer process, the lecturer plays an active role in the PBL as well as the students. There are several advantages and disadvantages of this method, starting from the process of identifying to discussing students conducted in a small class with a facilitator. Measures refer to seven jump steps.Theses seven jump steps must be completed in the PBL method. Aspect is an important part of an assessment, while an assessment component should be in line with the concept of PBL. There are two types of assessments, namely formative and summative. PBL method has also been applied in dentaleducation. In addition to pure PBL, there is a hybrid model described by Fincham and Shuler ( 2001). It is a model of